Analysis of Single Reservoir Dispatching During a Sudden Accident of Water Pollution in a Long Distance River Channel - FANG Shenguang; HUANG Daizhong; LAN Xiaofeng (Renmin Zhujiang)
This paper establishes the hydrodynamic model and mathematical pollutant transport and diffusion model of long distance river channel and cascade reservoir and verifies the models by analytic solutions of pollutant transport and diffusion, and sets up eleven dispatching modes of single reservoir and conducts simulation according to the sudden water pollution accident occurred at different locations at the upper or lower reaches of a reservoir. The results show that: when a sudden water pollution accident occurred at the lower reach, if the pollutant concentration is the sensitive factor of targeted lower reach, a dispatching mode with large flow and short duration is more appropriate for a short-distance reservoir at the upper reach. However, if the reservoir is too far away from the targeted reach, it is difficult to control the pollutant concentration in the targeted reach with the reservoir dispatching mode. If the out-of-limit time of pollutants is a sensitive factor of the targeted reach, a dispatching model with moderate flow and short duration is suitable for a reservoir within a proper distance from the targeted reach.When a sudden pollution accident occurred within a reservoir, if the reservoir area is an important functional area, the discharge facilities of the reservoir should be turned on as soon as possible to reduce the concentration and retention time of the pollutant in the reservoir. However, if the targeted lower reach is an important functional section, it is necessary to delay the turning on of the reservoir and reduce the discharge flow as much as possible to reduce the impact on the targeted lower reach.